Christianity and Christians in Shakī and Shīrvān from the Earliest Times Until the end of the Safavid Era - Kostikyan, Kristine; Stepanyan, Gevorg; Mkhitaryan, Gohar («Քոփի Փրինթ» տպագրատուն)
The paper examines the religious aspects of the history of Shakī and Shīrvān regions of Eastern Caucasus from the times of the spread of Christianity there until the end of Safavid rule over it. An overview of the history of the Church of Albania (or Ağuank‘), its legal and political aspects conducted in the article are important for a better understanding of its relations with the Armenian Apostolic Church, and identity issues of its subject Christian population. An empirical and comparative-historical analysis of the data and information con-tained in historical sources on the situation of Christians in the regions of Shakī and Shīrvān provides a clear view of the realities and situation in each phase of history and the factors stimulating their conversion to Islam. The study shows that during Safavid predominance over the regions included in one administrative unit of Shīrvān bīglarbīgī the cultural and civil methods of assimilation and conversion, combined with economic incentives, prevailed. The gradual weakening of Safavid rule over the regions was accompanied with serious challenges and hardships faced by local Christians during the frequent invasions of North Caucasian tribes. The collapse of Safavid rule in the regions designated the end of religious tolerance and intensification of the use of forced and economic methods of conversion to Islam. Քրիստոնեությունը, տարածված լինելով Աղվանքում Հայոց թագավորության աջակցությամբ 4-րդ դարում և ձևավորելով իր սեփական կրոնական կառույցը հանձին Աղվանից Եկեղեցու, ենթարկվում էր Ամենայն Հայոց կաթողիկոսին։ Հայոց Առաքելական եկեղեցին և նրա դավանանքը վաղ միջնադարից մինչև 19-րդ դարի վերջը վճռորոշ դեր են ունեցել Արևելյան Այսրկովկասի և մասնավորապես նաև Շաքի-Շիրվանի քրիստոնյաների ազգային ինքնագիտակցության, լեզվի, էթնիկ նկարագրի ու ինքնության պահպանության գործում, հակադրվել դավանափոխության գործընթացներին։ Աղվանից Եկեղեցին արաբական նվաճումից հետո առճակատվում է իսլամի տարածման իրողությանը, որը ժամանակի ընթացքում խարխլում է քրիստոնեության հիմքերը և նվազեցնում նրա հետևորդների քանակը տեղի քրիստոնյաների շարունակական մահմեդականացման միջոցով։ Սույն հոդվածով փորձ է արվում հետազոտել Շաքիի ու Շիրվանի շրջաններում ապրող քրիստոնյաներին վերաբերող աղբյուրագիտական նյութը՝ լուսաբանելով քրիստոնեության աստիճանական թուլացման հանգամանքները և քրիստոնյաների մահմեդականացման գործընթացը վաղ միջնադարից մինչև Սեֆյան տիրապետության ավարտը։ Քննվում են գործոնները, որոնք նպաստում էին քրիստոնյաների մահմեդականացմանը տարբեր ժամանակահատվածներում։ Դրանցից էին մահմեդական իշխանության պայմաններում քրիստոնյաների անհավասար իրավաքաղաքական ու սոցիալ-տնտեսական դրությունը նրանց տրված զիմմիի կարգավիճակում, նրանց նկատմամբ իշխանությունների խտրական վերաբերմունքը և Սեֆյան պետության ներսում քրիստոնյաների մահմեդականացումը խրախուսող սոցիալ-տնտեսական զանազան միջոցները, նաև Սեֆյան տիրապետության անկման շրջանում Հյուսիս-Կովկասյան լեռնաբնակ ցեղերի հաճախացած արշավանքների ընթացքում քրիստոնյաների նկատմամբ դրսևորվող կրոնական անհանդուրժողականությունը և բռնությունները։
Keywords: Christianity; History of Armenian church